Aspek Pidana Pelaksanaan Tugas Pemandu Lalu Lintas Penerbangan Dalam Kecelakaan Pesawat udara - Josi Edward Lakburlawal (Jurist-Diction, 2024)
As an archipelagic country, Indonesia is a country that is suitable for air transportation because it can connect all parts of Indonesia. With the large number of aircraft carrying out transportation, of course it will be very dangerous if there is no one to direct the pilots so that they can fly safely to their destinations, this is where the role of flight traffic guides becomes crucial. However, it is possible for flight traffic guides to commit criminal acts so that there are arrangements regarding the accountability of flight traffic guides regulated in the Criminal Code in Articles 470g, 470m, and 470o and also regulated in the Aviation Law in Articles 437 and 439, but regulations regarding The legal subject in the article is still general and not specific because it still uses the legal subject "whoever" and "everyone. However, if the officer is proven to have made a mistake or negligence that endangers the aircraft, of course the relevant officer can be held criminally responsible and may be subject to criminal charges. penalty.